Does It Matter Where You Live? Rural–Urban Context Among Women Entrepreneurs in Pakistan - Muhammad, Said; Ximei, Kong (Frontiers in Psychology, 2022)
Entrepreneurship is considered as one of the strategies for economic and regional development. In particular, women entrepreneurs engaged in different geographic locations, where their characteristics and business factors are different in each location. This study examines home-based women entrepreneurs in Pakistan in relation to their place of residence, specifically rural or urban context. Very few studies have considered place of residence as a variable affecting women’s businesses at the household level. This is critical since the business context can exert a major influence on available resources and constraints that affect business viability and sustainability. Data were collected from 504 women entrepreneurs using a survey questionnaire. Descriptive statistics, chi-square test, and binary logistics regression were used to achieve the objectives of the study. The findings revealed important and significant differences based on the rural versus urban context of women entrepreneurs including home ownership, household size, the number of adult family members in the household, family financial position, business record keeping, having a bank account, and type of business. While the binary logistic regression analysis reported adult family members, family financial position, business record keeping, bank account, and beautician business were the significant predictors of the women entrepreneurs’ rural–urban model. The findings offer implications for policymakers, funders, bank/financial institutions, and non-governmental organizations for increasing women’s entrepreneurship, empowerment, and income equality in developing countries.